A mobile-phone immunization record in Ontario: uptake and opportunities for improving public health. (December 2014) - Wilson, Kumanan; Atkinson, Katherine; Pluscauskas, Michael; Bell, Cameron
A free iPhone app was designed to help parents in Ontario track their children's vaccination records. It was launched in the iTunes app store on 20 November 2012. There were 4867 downloads in the following 12 months. We observed that downloads of the app were correlated with media coverage. Usage of the app was measured by app opens and the time spent in the app per open: on average there were 53 opens per day and 126 seconds spent per open. Users expressed concerns about the privacy of health information and accessibility by people of lower socioeconomic status, who were less likely to be smartphone owners. A national version of the app is now being developed for multiple mobile phone types. There is potential to develop additional features such as mobile adverse event reporting, vaccine vial barcode scanning and integration with immunization registries. Immunization is an area in which a mobile solution is very useful.